(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
This article discusses the issues of problems and educational institutions in the system of uninterrupted education, based on pedagogical properties of environmental education on the basis of young and mental properties of the educator in educational institutions.